Regulation and registration as drivers of continuous professional competence for Irish pre-hospital practitioners: a discussion paper. (May 2016) - Knox, S.; Dunne, S.; Hughes, M.; Cheeseman, S.; Dunne, C.
Abstract Background The regulatory body responsible for the registration of Irish pre-hospital practitioners, the Pre-Hospital Emergency Care Council (PHECC), identified the need to implement a continuing professional competence (CPC) framework. The first cycle of CPC (focused on emergency medical technicians) commenced in November 2013 creating for the first time a formal relationship between continuing competence and registration to practice. Aims To review current literature and to describe benefits and challenges relevant to CPC, regulation, registration and their respective contributions to professionalism of pre-hospital practitioners: advanced paramedics, paramedics and emergency medical technicians. Methods Online search of cumulative index to nursing and allied health literature (CINAHL Plus with Full Text), Allied and Complementary Medicine (AMED) and 'Pubmed' databases using: 'Continuous Professional Development'; 'Continuous Professional Development'; 'emergency medical technician'; 'paramedic'; 'registration'; 'regulation'; and "profession' for relevant articles published since 2004. Additional policy documents, discussion papers, and guidance documents were identified from bibliographies of papers found. Results Reports, governmental policies for other healthcare professions, and professional developments internationally for allied professions (e.g., nursing, physiotherapy and medicine) link maintenance of competence with requirements for registration to practice. Conclusion We suggest that evolving professionalisation of Irish paramedics should be affirmed through behaviours and competencies that incorporate adherence to professional codes of conduct, reflective practice, and commitment to continuing professional development. While the need for ambulance practitioner CPD was identified in Ireland almost a decade ago, PHECC now has the opportunity to introduce a model of CPD for paramedics linking competence and professionalism to annual registration.